Revisão histórica de infecção experimental por leptospiras em ruminantes - Ribeiro, B.; Martins, G.; Lilenbaum, W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is an infectious diseasecaused by pathogenic spirochetes of the genus Leptospira. It affects domestic and wild animals and is characterized as a zoonotic disease. Leptospiral infectioncauses significant economic losses to livestock, mainly due to abortions, premature births, stillbirths, and weak calf syndrome. The first studies performed on this subject were focused on the observation of the pathological alterations caused by the inoculation of serovar Pomona in cows, reproducing the acute disease,with jaundice, hematuria, fever, and abortions. In other decades, other experimental infections were conducted in ruminants, describing the clinical presentationof the infection by Hardjo and other serovars, with a large variation of the clinical signs as fever, abortion, prostration, mastitis, placenta retention.